A small 7q11.23 microduplication involving GTF2I in a family with intellectual disability. Issue 6 (29th April 2020) - Pinelli, Michele; Terrone, Gaetano; Troglio, Flavia; Squeo, Gabriella Maria; Cappuccio, Gerarda; Imperati, Floriana; Pignataro, Piero; Genesio, Rita; Nitch, Lucio; Del Giudice, Ennio; Merla, Giuseppe; Testa, Giuseppe; et al.
Abstract :